High toxinogenic potential of Staphylococcus aureus from wild ungulates in Brandenburg, Germany with a low level of antibiotic resistance - Lienen, Tobias; Mateus-Vargas, Rafael Hernán; Steinhoff-Wagner, Julia; Richter, Martin H.; Maurischat, Sven (Frontiers in Veterinary Science, 2024)
Data regarding the occurrence and virulence of Staphylococcus (S.) aureus in wild living animals is rare. However, S. aureus may carry a multitude of virulence factors and express resistance to several antimicrobial substances. Handling game meat may thus lead to serious infections or food poisoning. The aim of this study was to provide insights into the occurrence and characteristics of S. aureus in wild ungulates from Brandenburg, Germany. Nasal swabs of externally healthy-looking wild boars, roe, fallow and red deer were collected in hunts during season 2021/2022 and analyzed for S. aureus by selective enrichment. Species were determined using matrix assisted laser desorption ionization mass spectrometry and tested for phenotypic antimicrobial resistance. Whole-genome sequencing was conducted for genotyping, determination of virulence associated genes and analysis of phylogenetic relationships. S. aureus were recovered from approximately 8% of nasal swabs. However, the strains were only obtained from the sampled wild ruminants. S. aureus isolates were associated with sequence types (ST) 1, ST30, ST133, ST425, ST582 and ST6238. Isolates of ST1 clustered closely together in the phylogenetic analysis. Genes encoding staphylococcal enterotoxin (SE) or SE-like (SEl) were found in 14/17 isolates. In particular, a seh gene was present in 12/17 isolates. Moreover, two isolates harbored a multiplicity of genes encoding SE or SEl. In addition, the toxic shock syndrome toxin encoding tst gene was detected in one isolate. This isolate was resistant to penicillin and cefoxitin and accordingly harbored the blaZ gene. Wild ungulates intended for human consumption may carry potentially virulent S. aureus. In one case, the close phylogenetic relationship of S. aureus isolates indicates a possible intraspecific spread within a common territory. However, for others, the origin or the spread pattern can only be inferred. Handling of animals or their carcasses might contribute to staphylococcal infections in humans. Moreover, food poisoning due to SE producing strains may occur, if recommended hygiene practices are not applied during processing of game meat.